Atypical Eclampsia in a Pregnant Woman Infected by COVID-19 - Maha Ahmad Odeh; Yousef S. Abuzneid; Omar Badareen; Khaled Masarweh (Case Reports in Obstetrics and Gynecology)
The coronavirus disease 2019, also called (COVID-19), is an infectious disease which is caused by a virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The first report was in December 2019, and on March 12, 2020, the World Health Organization (WHO) declared this disease a pandemic. COVID-19 targets many major organs causing life-threatening systemic complications. It can cause lung damage and respiratory failure in addition to systemic inflammation and immune dysregulation. Hypercoagulable state and numerous neurological abnormalities also have been reported due to this condition. Going through the literature review, we found some cases of pregnant women with novel coronavirus infection, being mostly mild illnesses, and most of these cases were focused on maternal-fetal transmission and neonatal outcomes. In this case report, we present the case of a COVID-19 positive woman who came to our emergency department at 34 weeks of gestation with tonic-clonic seizures. This case was a challenge for us because we faced a new an unknown manifestation of both COVID and eclampsia.